The kachina and the cross : Indians and Spaniards in the early Southwest - Riley, Carroll L. (University of Utah Press, 1999)
"In The Kachina and the Cross Carroll Riley weaves elements of archaeology, history, and anthropology to tell a dramatic story of conflict in the seventeenth century. This fresh look at a crucial period in Southwestern history builds on Riley's recent work Rio del Norte: People of the Upper Rio Grande from Earliest Times to the Pueblo Revolt."--Jacket